Chinese Christians in America: Conversion, Assimilation, and Adhesive Identities - Yang, Fenggang (Penn State University Press, 1999)
Front -- Contents -- Preface -- Introduction: Studying Chinese Christians in the United States -- 1 Assimilation, Ethnicity, and Religion -- 2 Chinese Immigrants, Cultural Traditions, and Changing Identities -- 3 Becoming Christian -- 4 Becoming American -- 5 Preserving Chinese Culture -- 6 Deconstructing the Chinese Identity, Reconstructing Adhesive Identities -- Conclusion: Pluralism and Adhesive Identities -- Appendix: The Chinese Christian Church of Greater Washington, D.C.: An Annotated Chronology -- Notes -- Bibliography -- Index -- Back.